Encyclopedia of women and baseball - Heaphy, Leslie A., 1964-; May, Mel Anthony (McFarland & Co., 2006)
"This encyclopedia provides information on women players, managers, teams, leagues, and issues since the mid-19th century. Players are listed by maiden name with married name, when known, in parentheses. Information provided includes birth date, death date, team, dates of play, career statistics and brief biographical notes when available"--Provided by publisher.